England - Escott, John (Oxford University Press, 2008)
The "Factfiles" are non-fiction readers for all ages, featuring a wide range of topics such as famous cities, sport, science, the environment and the media. Colour photographs complement the text and there are exercises at the back of each book to check students' understanding, plus ideas for extended activities and project work. The books are ideal for cultural and cross-curricular studies and selected titles are also available on cassette and CD. Every year millions of people visit England from all over the world. Find out why and read about the history of the country and some of the things you can see and do there today - the cities, national parks, sports, the cinema and theatre, pubs and music. All the things that make England a beautiful and exciting place to visit!